Preparation method of bimetallic doped porous carbon-based bifunctional electrocatalyst
Patent Information
- Application Number
- CN202310783405.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-29
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2043-06-29
AI Technical Summary
[0004]本发明提供了一种双金属掺杂多孔碳基双功能电催化剂的制备方法,解决现有氧还原电催化剂制备难、活性低、成本高等技术难题,并为制备氧还原和氧析出双功能催化剂提供了参考;很好的解决了双金属前驱体的制备难的问题;推动双金属碳基多孔材料电催化的研究
1、本发明采用金属有机框架(MOF)材料作为前驱体,有利于活性位点稳定性的提高;
Smart Images

Figure CN116864712B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the fields of nanomaterials technology and electrochemical catalysis, and particularly relates to a method for preparing a bimetallic doped porous carbon-based bifunctional electrocatalyst. Background Technology
[0002] In recent years, rechargeable zinc-air (Zn-air) batteries have received particular attention in practical applications. Zn-air batteries have a high energy density (1350 Wh kg⁻¹). -1 Zn-air batteries offer advantages such as low cost, environmental friendliness, and high safety. The performance of Zn-air batteries during charge and discharge primarily depends on the oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) at the cathode. However, both ORR and OER involve slow kinetics and complex multi-electron transfer steps, necessitating the use of electrocatalysts to accelerate these processes. Currently, the most active catalysts for ORR and OER are Pt-based and RuO2 / IrC noble metal materials. However, their scarcity, high cost, low stability, and single functionality limit their widespread application. Therefore, there is an urgent need to find bifunctional catalysts that are abundant, stable, and inexpensive.
[0003] In recent years, transition metal nitrogen-carbon (MNC) materials have attracted widespread attention, with the potential to replace noble metal-based catalysts. MNCs can provide dual highly active sites for both ORR and OER. Despite some progress, the catalytic performance of these catalysts still needs to be enhanced to achieve the commercialization of rechargeable Zn-air batteries. Carbon materials with bimetallic (Fe / Co) and N dopants have been reported to possess abundant active sites, making them suitable bifunctional electrocatalysts for Zn-air batteries. However, synthesizing ideal Fe / Co-NC bifunctional electrocatalysts through precise control of composition and structure is challenging. Therefore, intelligent selection and integration of Fe / Co-NC precursors are crucial during active site formation. Summary of the Invention
[0004] This invention provides a method for preparing bimetallic doped porous carbon-based bifunctional electrocatalysts, solving the technical problems of difficult preparation, low activity, and high cost of existing oxygen reduction electrocatalysts, and providing a reference for the preparation of oxygen reduction and oxygen evolution bifunctional catalysts; it also effectively solves the problem of difficult preparation of bimetallic precursors; and promotes the research on electrocatalysis of bimetallic carbon-based porous materials.
[0005] A method for preparing a bimetallic doped porous carbon-based bifunctional electrocatalyst involves first synthesizing MIL-53 via a solvothermal method, and then uniformly mixing a certain proportion of ZIF-67 and MIL-53 by simple ball milling under electrostatic and pressure conditions to obtain MIL / ZIF-x; subsequently, calcining at high temperature yields un-acid-washed MIL / ZIF-x-700℃, and finally, acid washing and NH3 activation yields MIL / ZIF-x-700℃-NH3. The specific preparation steps are as follows: Step S1: Preparation of ZIF-67: Weigh 1.164 g of cobalt salt and add it to 50 mL of methanol solution, stirring vigorously for about 1 h, denoted as solution A; add 0.5~1.5 mg of 2-methylimidazole to 50 mL of methanol solution, stirring vigorously for about 1 h, denoted as solution B; then pour solution B into solution A, and stir vigorously at room temperature for 12 h; subsequently, wash three times with methanol solution by centrifugation; after vacuum drying, ZIF-67 is harvested; the cobalt salt is any one of cobalt sulfate, cobalt chloride, cobalt nitrate, or cobalt acetate; Step S2: Preparation of MIL-53: Weigh 540 mg of iron salt and 500-800 mg of PTA and dissolve them in 50 mL of DMF solution, stirring vigorously for 1 h; then place the mixture into an autoclave, and then place the autoclave into an oven, heating to 120-180℃ and maintaining for 12 h before cooling to room temperature; subsequently, wash three times with DMF solution by centrifugation; after vacuum drying, obtain yellowish-brown MIL-53; the iron salt is any one of ferrous sulfate, ferric chloride, ferric nitrate, or ferric acetate; Step S3: Preparation of MIL / ZIF-x-700℃-NH3: 1000~200 mg of MIL-53 and ZIF-67 in a mass ratio of (6~1):1 were mixed uniformly by ball milling for 1 min to obtain the MIL / ZIF-x precursor, where x represents the mass ratio of MIL-53 to ZIF-67; MIL / ZIF-x was placed in a tube furnace and heated to 200℃ at a flow rate of 300 sccm in a N2 atmosphere at a rate of 5℃ / min, and held for 2 h, then heated to 600℃~900℃ and held for 2 h, and then cooled to room temperature to obtain un-acid-washed MIL / ZIF-x-700℃ powder; the un-acid-washed MIL / ZIF-x-700℃ was acid-washed in 3M HNO3, sonicated at 80℃ for 2 h, and allowed to stand for 8 hours. h; then the sample was vacuum extracted and filtered with deionized water to make the sample neutral, and then placed in a vacuum drying oven at 40℃ for 12 h; finally, the acid-washed MIL / ZIF-x-700℃ powder was obtained, and the acid-washed MIL / ZIF-x-700℃ was placed in a tube furnace, heated to a certain temperature in a mixed gas atmosphere, held for 2 h, and then cooled to room temperature to finally obtain MIL / ZIF-x-700℃-NH3 powder.
[0006] Preferably, the mixed gas in step S3 of the present invention is ammonia and nitrogen.
[0007] The bimetallic-doped porous carbon-based bifunctional electrocatalyst prepared using the method of the present invention has the following advantages compared with the prior art: 1. This invention uses metal-organic framework (MOF) materials as precursors, which is beneficial to improving the stability of active sites; 2. This invention uses a one-step grinding method to combine two MOFs together through electrostatic forces, providing a good method for preparing bimetallic precursors with a simple preparation process; 3. The catalyst prepared by this invention exhibits superior ORR / OER electrocatalytic performance and has better stability than commercial 20wt% Pt / C and RuO2, which is very advantageous for long-term use; 4. The bifunctional electrocatalyst of the present invention is Fe / Co-NC, and the raw materials used are easy to prepare, abundant and inexpensive, resulting in low cost for large-scale preparation; the preparation method of this catalyst is simple, easy to operate, and convenient for large-scale production. 5. The zinc-air battery assembled using this catalyst exhibits superior discharge performance compared to a commercially available zinc-air battery assembled with 20 wt% Pt / C. Furthermore, it demonstrates excellent charge-discharge performance, which is of significant theoretical and practical importance for the development of rechargeable zinc-air batteries. Attached Figure Description
[0008] Figure 1 The synthesis process diagrams are for the catalysts MIL / ZIF-x-700℃-NH3 obtained in Examples 1-4, the catalyst ZIF-67-700℃-NH3 obtained in Comparative Example 1, and the catalyst MIL-53-700℃-NH3 obtained in Comparative Example 2. Figure 2 The linear sweep voltammetry (LSV) plots of the catalyst MIL / ZIF-4-700℃-NH3 obtained in Example 3 were obtained before and after 5000 and 10000 CV cycles performed at a sweep rate of 100 mV / s in a 0.1 M KOH electrolyte saturated with O2, at a rotation speed of 1600 rpm. Figure 3 LSV plots of the catalyst 20wt% Pt / C for Comparative Example 4 were obtained before and after 5000 CV cycles in 0.1 M KOH electrolyte saturated with O2 at a rotation speed of 1600 rpm and a scan rate of 100 mV / s. Figure 4 The methanol resistance test curves of the catalyst MIL / ZIF-4-700℃-NH3 obtained in Example 3 and the catalyst 20wt% Pt / C in Comparative Example 4 are shown. Figure 5 Chronoamperometry curves of the catalyst MIL / ZIF-4-700℃-NH3 obtained in Example 3 and the catalyst 20wt% Pt / C in Comparative Example 4 are shown. Figure 6 The discharge polarization curves and corresponding power densities of Zn-air batteries using MIL / ZIF-4-700℃-NH3, 20wt% Pt / C and RuO2+20wt% Pt / C as catalysts, respectively; Figure 7 For 10 mA cm -2 Long-term discharge test curves of Zn-air cells using the catalyst MIL / ZIF-4-700℃-NH3 obtained in Example 3 and the catalyst 20wt% Pt / C of Comparative Example 4 as cathode catalysts at current densities are shown in the figure. (The inset is an optical photograph of the supply timer of a Zn-air cell using the catalyst MIL / ZIF-4-700℃-NH3 obtained in Example 3 as cathode catalyst.) Figure 8 The full polarization curves of the catalyst MIL / ZIF-4-700℃-NH3 obtained in Example 3 and the catalyst 20wt% Pt / C and RuO2 in Comparative Example 4 were tested at 0.1 M KOH electrolysis pressure. Figure 9 For 5 mA cm -2Long-term charge-discharge test curves of Zn-air batteries using the catalyst MIL / ZIF-4-700℃-NH3 obtained in Example 3 and the catalyst 20wt% Pt / C of Comparative Example 4 as catalysts were obtained at current densities. Detailed Implementation
[0009] To further understand the present invention, the following description, in conjunction with the accompanying drawings and embodiments, will further illustrate the present invention, but does not limit the present invention in any way.
[0010] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used herein in the specification of this invention is for the purpose of describing particular embodiments only and is not intended to be limiting of the invention. The term "and / or" as used herein includes any and all combinations of one or more of the associated listed items.
[0011] In embodiments of the present invention, the specific sources of the various materials are as follows: Terephthalic acid (PTA): Shanghai Aladdin Biochemical Technology Co., Ltd.; Ferric chloride: Shanghai Aladdin Biochemical Technology Co., Ltd.; Cobalt nitrate: Shanghai Aladdin Biochemical Technology Co., Ltd.; N,N-Dimethylformamide (DMF): Shanghai Aladdin Biochemical Technology Co., Ltd.; Dimethylimidazole: Shanghai Aladdin Biochemical Technology Co., Ltd. Concentrated hydrochloric acid (HCl): Sinopharm Chemical Reagent Co., Ltd. Ethanol: Anhydrous ethanol, Sinopharm Chemical Reagent Co., Ltd.; 5 wt% Nafion: DuPont; Commercial 20wt% Pt / C: Sigma-Aldrich LLC.; Potassium hydroxide (KOH): Shanghai Aladdin Biochemical Technology Co., Ltd. Zinc acetate (Zn(Ace)2): Shanghai Aladdin Biochemical Technology Co., Ltd. Methanol: Sinopharm Chemical Reagent Co., Ltd.; Deionized water: homemade.
[0012] The following embodiments of the present invention illustrate the testing process for Zn-air battery performance:
[0013] The performance of the Zn-air battery was tested using a self-made battery device. The air cathode consisted of four layers: a waterproof membrane, nickel foam current collector, and a catalyst-coated surface on hydrophilic carbon paper. A mixed solution of 0.2 M Zn(Ace)₂ and 6 M KOH was used as the electrolyte. A polished zinc plate served as the anode. The charge and discharge performance of the Zn-air battery was tested using an electrochemical workstation. Cyclic tests were performed, consisting of 15 minutes of charging followed by 15 minutes of discharging.
[0014] A method for preparing a bimetallic-doped porous carbon-based bifunctional electrocatalyst involves first synthesizing ZIF-67 via a simple chemical method. Additionally, MIL-53 is synthesized via a solvothermal method. ZIF-67 and MIL-53 are then uniformly mixed in a specific ratio using a simple ball milling method under electrostatic and pressure conditions to obtain MIL / ZIF-x. This mixture is then calcined at high temperature to obtain un-acid-washed MIL / ZIF-x-700℃, and finally activated with NH3 to obtain MIL / ZIF-x-700℃-NH3. The specific preparation steps are as follows: Preparation of ZIF-67 (S1): 1.164 g of cobalt salt was weighed and added to 50 mL of methanol solution, and stirred vigorously for about 1 h; this is designated as solution A. 0.5–1.5 mg of 2-methylimidazole was added to 50 mL of methanol solution and stirred vigorously for about 1 h; this is designated as solution B. Solution B was then poured into solution A, and the mixture was stirred vigorously at room temperature for 12 h. The sample was then washed three times by centrifugation with methanol solution. ZIF-67 was then harvested after vacuum drying. The cobalt salt was any one of cobalt sulfate, cobalt chloride, cobalt nitrate, or cobalt acetate.
[0015] Preparation of S2: MIL-53: Weigh 540 mg of ferric salt and 500-800 mg of PTA and dissolve them in 50 mL of DMF solution, stirring vigorously for 1 h. Then, place the mixture in an autoclave. Next, place the autoclave in an oven and heat to 120-180℃, maintaining this temperature for 12 h before cooling to room temperature. The sample is then washed three times by centrifugation with DMF solution. Finally, the sample is vacuum dried to obtain a yellowish-brown MIL-53. The ferric salt can be any one of ferrous sulfate, ferric chloride, ferric nitrate, or ferric acetate.
[0016] Preparation of S3: MIL / ZIF-x-700℃-NH3: 1000~200 mg of MIL-53 and ZIF-67 ((6~1):1) in different mass ratios were mixed uniformly by ball milling for 1 min to obtain the MIL / ZIF-x precursor (x represents the mass ratio of MIL-53 to ZIF-67, x=6~1, 1). MIL / ZIF-x was placed in a tube furnace and heated to 200℃ at a flow rate of 300 sccm in a N2 atmosphere at a rate of 5℃ / min, and held for 2 h. Then, it was heated to 600℃~900℃ in the tube furnace at a heating rate of 5℃ / min and held for 2 h. Afterward, it was cooled to room temperature to obtain un-acid-washed MIL / ZIF-x-700℃ powder. The un-acid-washed MIL / ZIF-x-700℃ was acid-washed in 3M HNO3 and sonicated at 80℃ for 2 h. Then let it stand for 8 hours. Next, vacuum extract and filter the sample with deionized water to neutralize it. Then, dry it in a vacuum drying oven at 40°C for 12 hours. Finally, obtain the acid-washed MIL / ZIF-x-700°C powder. Place the acid-washed MIL / ZIF-x-700°C powder in a tube furnace, heat it to a certain temperature in a mixed gas atmosphere, hold it at that temperature for 2 hours, and then cool it to room temperature. Finally, obtain the MIL / ZIF-x-700°C-NH3 powder. The mixed gas consisted of ammonia and nitrogen. Example 1
[0017] 400 mg of a mixture of MIL-53 and ZIF-67 (mass ratio = 1:1) was ball-milled for 1 min to obtain a MIL / ZIF-1 precursor (1 indicates a mass ratio of MIL-53 to ZIF-67 = 1:1). The MIL / ZIF-1 was placed in a tube furnace under a N2 atmosphere at a flow rate of 300 sccm, heated to 200 °C at a rate of 5 °C / min, and held for 2 h. It was then heated to a further temperature and held for 2 h, before being cooled to room temperature to obtain un-acid-washed MIL / ZIF-x-700 °C powder. The un-acid-washed MIL / ZIF-x-700 °C was acid-washed in 3 M HNO3 and sonicated at 80 °C for 2 h. It was then allowed to stand for 8 h. The sample was then vacuum-extracted and filtered with deionized water to neutralize it. Finally, it was dried in a vacuum drying oven at 40 °C for 12 h. Finally, the acid-washed MIL / ZIF-1-700℃ powder was obtained. The acid-washed MIL / ZIF-1-700℃ powder was placed in a tube furnace and heated to a certain temperature in a mixed gas atmosphere, held at that temperature for 2 hours, and then cooled to room temperature. Finally, MIL / ZIF-1-700℃-NH3 powder was obtained. Example 2
[0018] 400 mg of a mixture of MIL-53 and ZIF-67 (mass ratio = 2:1) was ball-milled for 1 min to obtain a MIL / ZIF-2 precursor (2 represents the mass ratio of MIL-53 to ZIF-67, x = 2:1). The MIL / ZIF-2 was placed in a tube furnace under a N2 atmosphere at a flow rate of 300 sccm, heated to 200 °C at a rate of 5 °C / min, and held for 2 h. It was then heated to a further temperature and held for 2 h, before being cooled to room temperature to obtain un-acid-washed MIL / ZIF-x-700 °C powder. The un-acid-washed MIL / ZIF-x-700 °C was acid-washed in 3 M HNO3 and sonicated at 80 °C for 2 h. It was then allowed to stand for 8 h. The sample was then vacuum-extracted and filtered with deionized water to neutralize it. Finally, it was dried in a vacuum drying oven at 40 °C for 12 h. Finally, the acid-washed MIL / ZIF-2-700℃ powder was obtained. The acid-washed MIL / ZIF-2-700℃ powder was placed in a tube furnace and heated to a certain temperature in a mixed gas atmosphere, held at that temperature for 2 hours, and then cooled to room temperature. Finally, MIL / ZIF-2-700℃-NH3 powder was obtained. Example 3
[0019] 400 mg of a mixture of MIL-53 and ZIF-67 (mass ratio = 4:1) was ball-milled for 1 min to obtain a MIL / ZIF-4 precursor (4 indicates a mass ratio of MIL-53 to ZIF-67 of 4:1). The MIL / ZIF-4 precursor was placed in a tube furnace under a nitrogen atmosphere at a flow rate of 300 sccm, heated to 200 °C at a rate of 5 °C / min, and held for 2 h. It was then heated to a further temperature and held for 2 h, before being cooled to room temperature to obtain un-acid-washed MIL / ZIF-x-700 °C powder. The un-acid-washed MIL / ZIF-x-700 °C was acid-washed in 3 M HNO3 and sonicated at 80 °C for 2 h. It was then allowed to stand for 8 h. The sample was then vacuum-extracted and filtered with deionized water to neutralize it. Finally, it was dried in a vacuum drying oven at 40 °C for 12 h. Finally, the acid-washed MIL / ZIF-4-700℃ powder was obtained. The acid-washed MIL / ZIF-4-700℃ powder was placed in a tube furnace and heated to a certain temperature in a mixed gas atmosphere, held at that temperature for 2 hours, and then cooled to room temperature. Finally, MIL / ZIF-4-700℃-NH3 powder was obtained.
[0020] Figure 2The linear sweep voltammetry (LSV) plots of the catalyst MIL / ZIF-4-700℃-NH3 obtained in Example 3 of this invention are shown. The catalyst was tested in a 0.1 M KOH electrolyte saturated with O2 at 1600 rpm with a scan rate of 100 mV / s for 5000 and 10000 CV cycles. The results show that the catalyst obtained in this invention exhibits good cycling stability. Example 4
[0021] 400 mg of a mixture of MIL-53 and ZIF-67 (mass ratio = 6:1) was ball-milled for 1 min to obtain a MIL / ZIF-6 precursor (6 indicates a mass ratio of MIL-53 to ZIF-67 of 6:1). The MIL / ZIF-6 precursor was placed in a tube furnace under a N2 atmosphere at a flow rate of 300 sccm, heated to 200 °C at a rate of 5 °C / min, and held for 2 h. It was then heated to a further temperature and held for 2 h, before being cooled to room temperature to obtain un-acid-washed MIL / ZIF-x-700 °C powder. The un-acid-washed MIL / ZIF-x-700 °C was acid-washed in 3 M HNO3 and sonicated at 80 °C for 2 h. It was then allowed to stand for 8 h. The sample was then vacuum-extracted and filtered with deionized water to neutralize it. Finally, it was dried in a vacuum drying oven at 40 °C for 12 h. Finally, the acid-washed MIL / ZIF-6-700℃ powder was obtained. The acid-washed MIL / ZIF-6-700℃ powder was placed in a tube furnace and heated to a certain temperature in a mixed gas atmosphere, held at that temperature for 2 hours, and then cooled to room temperature. Finally, MIL / ZIF-6-700℃-NH3 powder was obtained.
[0022] Comparative Example 1: Preparation of ZIF-67-700℃-NH3: 200 mg of ZIF-67 was placed in a ball mill jar and milled for 1 min. The sample was then placed in a tube furnace, N2 was introduced, and the temperature was raised to 200℃ at a rate of 5℃ / min and held for 2 h. The temperature was then raised to 700℃ at a rate of 5℃ / min and held for 2 h, followed by cooling to room temperature. The heat-treated powder was then acid-washed in 3M HNO3 and sonicated at 80℃ for 2 h. The mixture was then allowed to stand for 8 h. The sample was then vacuum-extracted and filtered with deionized water to achieve neutrality. It was then dried in a vacuum drying oven at 40℃ for 12 h. The dried sample was then placed in a tube furnace, and a mixture of NH3 and N2 was introduced at a flow rate of 300 sccm. The temperature was raised to 900℃ at a rate of 10℃ / min and held for 2 h, followed by cooling to room temperature. Finally, ZIF-67-700℃-NH3 powder was obtained.
[0023] Comparative Example 2: Preparation of MIL-53-700℃-NH3: 200 mg of MIL-53 was placed in a ball mill jar and ball-milled for 1 min. The sample was then placed in a tube furnace, and N2 was introduced at a flow rate of 300 sccm. The temperature was increased to 200℃ at a rate of 5℃ / min and held for 2 h. Then, the temperature was increased to 700℃ at a rate of 5℃ / min and held for 2 h before cooling to room temperature. The heat-treated powder was then acid-washed in 3 M HNO3 and sonicated at 80℃ for 2 h. The mixture was then allowed to stand for 8 h. The sample was then vacuum-extracted and filtered with deionized water to neutralize it. It was then dried in a vacuum drying oven at 40℃ for 12 h. Next, the sample was placed in a tube furnace, and in a mixed atmosphere of NH3 and N2, the temperature was increased to 900℃ at a flow rate of 300 sccm and held for 2 h. The temperature was then reduced to room temperature to obtain MIL-53-700℃-NH3 powder.
[0024] Comparative Example 3: Preparation of MIL / ZIF-4-700℃ after pickling: 400 mg of a mixture of MIL-53 and ZIF-67 (mass ratio = 4:1) was ball-milled for 1 min to obtain the MIL / ZIF-4 precursor (4 represents the mass ratio of MIL-53 to ZIF-67 = 4:1). The MIL / ZIF-4 was placed in a tube furnace under a N2 atmosphere at a flow rate of 300 sccm, heated to 200℃ at a rate of 5℃ / min, and held for 2 h. Then, it was heated to 700℃ at a rate of 5℃ / min and held for 2 h. Afterward, it was cooled to room temperature to obtain un-acid-washed MIL / ZIF-x-700℃ powder. The un-acid-washed MIL / ZIF-x-700℃ was acid-washed in 3M HNO3 and sonicated at 80℃ for 2 h. It was then allowed to stand for 8 h. Finally, the sample was vacuum-extracted and filtered with deionized water to neutralize the sample. Then it was placed in a vacuum drying oven and dried at 40°C for 12 hours. Finally, the acid-washed MIL / ZIF-4-700°C powder was obtained.
[0025] Comparative Example 4: Commercial 20wt% Pt / C catalyst.
[0026] Figure 3 The LSV plots are for the catalyst 20wt% Pt / C of Comparative Example 4, which was tested in a 0.1 M KOH electrolyte saturated with O2 at a rotation speed of 1600 rpm and a sweep rate of 100 mV / s for 5000 CV cycles before and after. Compared with the catalyst 20wt% Pt / C of Comparative Example 4, the catalyst prepared in Example 3 of this invention has good cycle stability, which is superior to the commercial 20wt% Pt / C catalyst.
[0027] Figure 4 The graphs show the methanol tolerance test curves of the catalyst MIL / ZIF-4-700℃-NH3 obtained in Example 3 of the present invention and the catalyst 20wt%Pt / C in Comparative Example 4. It can be seen from the graphs that the catalyst obtained in Example 3 of the present invention has good methanol tolerance, which is better than that of the commercial 20wt%Pt / C catalyst.
[0028] Figure 5 The chronoamperometry curves are for the catalyst MIL / ZIF-4-700℃-NH3 obtained in Example 3 and the catalyst 20wt% Pt / C in Comparative Example 4. It can be seen from the curves that the catalyst of Example 3 obtained in this invention has good stability, which is superior to the commercial 20wt% Pt / C catalyst.
[0029] Figure 6 The discharge polarization curves and corresponding power densities of Zn-air batteries using MIL / ZIF-4-700℃-NH3, 20wt% Pt / C, and RuO2+20wt% Pt / C as catalysts are shown. It can be seen that the Zn-air battery using MIL / ZIF-4-700℃-NH3 as the cathode catalyst in Example 3 of this invention discharges at a current density of 271.6 mA cm⁻¹. -2 It has a peak power density of 176.3 mW / cm³. -2 The value was higher than that of the comparative example 4 (20wt% Pt / C, 141.8 mW cm⁻¹). -2 ) and 20wt%Pt / C+RuO2 (94.4 mW cm -2 The peak power density of the battery.
[0030] Figure 7 For 10 mA cm -2 Long-term discharge test curves of Zn-air batteries using the catalyst MIL / ZIF-4-700℃-NH3 obtained in Example 3 and the catalyst 20wt% Pt / C of Comparative Example 4 as cathode catalysts were obtained at current densities. (The inset is an optical photograph of the supply timer of a Zn-air battery using the catalyst MIL / ZIF-4-700℃-NH3 obtained in Example 3 as the cathode catalyst). It can be seen that the Zn-air battery with MIL / ZIF-4-700℃-NH3 obtained in Example 3 as the cathode catalyst has better constant current discharge durability than the commercial 20wt% Pt / C catalyst of Comparative Example 4.
[0031] Figure 8The full polarization curves of the catalyst MIL / ZIF-4-700℃-NH3 obtained in Example 3 and the catalyst 20wt% Pt / C and RuO2 in Comparative Example 4 were tested under an electrolytic pressure of 0.1 M KOH. It can be seen from the curves that the bifunctional catalytic performance of the catalyst MIL / ZIF-4-700℃-NH3 obtained in Example 3 is relatively good.
[0032] Figure 9 For 5 mA cm -2 Long-term charge-discharge test curves of Zn-air batteries using the catalyst MIL / ZIF-4-700℃-NH3 obtained in Example 3 and the catalyst 20wt% Pt / C of Comparative Example 4 as catalysts were obtained at current density. It can be seen from the results that the catalyst MIL / ZIF-4-700℃-NH3 obtained in Example 3 not only has high intrinsic catalytic activity and durability, but also enables Zn-air batteries to have high round-trip efficiency and long cycle life.
[0033] Table 1:
[0034] Table 1 summarizes the experimental results of the above embodiments and comparative examples, including the initial potentials of each embodiment and comparative example (…). E onset ), half-wave potential ( E 1 / 2 Limiting current () j lim ), number of transferred electrons ( N The corresponding data for the conversion rate of hydrogen peroxide (H2O 2%) and precursor mass ratio (4:1) were provided. Example 3, with a precursor mass ratio of 4:1, exhibited the best ORR performance, even surpassing the commercial 20wt% Pt / C precursor in Comparative Example 4. E onset =1.01 V vs RHE, E 1 / 2 =0.875 V vs. RHE, j lim = 5.8 mA cm -2 Its performance is superior and also better than most reported non-precious metal ORR electrocatalysts.
[0035] Figure 1 The diagram shows the synthesis process of catalysts MIL / ZIF-x-700℃-NH3 obtained in Examples 1-4 of the present invention, catalyst ZIF-67-700℃-NH3 obtained in Comparative Example 1, and catalyst MIL-53-700℃-NH3 obtained in Comparative Example 2. It can be seen from the diagram that the catalysts prepared by the present invention have a simple preparation process, are easy to operate, and are suitable for large-scale production.
Claims
1. A method for preparing a bimetallic-doped porous carbon-based bifunctional electrocatalyst, characterized in that: MIL-53 was first synthesized via a solvothermal method. Then, a certain proportion of ZIF-67 and MIL-53 were uniformly mixed by simple ball milling under electrostatic and pressure conditions to obtain MIL / ZIF-x. Next, un-acid-washed MIL / ZIF-x-700℃ was obtained by high-temperature calcination. Finally, MIL / ZIF-x-700℃-NH3 was obtained by acid washing and NH3 activation. The specific preparation steps are as follows: Step S1: Preparation of ZIF-67: Weigh 1.164 g of cobalt salt and add it to 50 mL of methanol solution, stirring vigorously for 1 h, denoted as solution A; add 0.5~1.5 mg of 2-methylimidazole to 50 mL of methanol solution, stirring vigorously for 1 h, denoted as solution B; then pour solution B into solution A, and stir vigorously at room temperature for 12 h; subsequently, wash three times with methanol solution by centrifugation; after vacuum drying, ZIF-67 is harvested; the cobalt salt is any one of cobalt sulfate, cobalt chloride, cobalt nitrate, or cobalt acetate; Step S2: Preparation of MIL-53: Weigh 540 mg of iron salt and 500-800 mg of PTA and dissolve them in 50 mL of DMF solution, stirring vigorously for 1 h; then place the mixture into an autoclave, and then place the autoclave into an oven, heating to 120-180℃ and maintaining for 12 h before cooling to room temperature; subsequently, wash three times with DMF solution by centrifugation; after vacuum drying, obtain yellowish-brown MIL-53; the iron salt is any one of ferrous sulfate, ferric chloride, ferric nitrate, or ferric acetate; Step S3: Preparation of MIL / ZIF-x-700℃-NH3: 1000~200 mg of MIL-53 and ZIF-67 in a mass ratio of (6~1):1 were mixed uniformly by ball milling for 1 min to obtain the MIL / ZIF-x precursor, where x represents the mass ratio of MIL-53 to ZIF-67; MIL / ZIF-x was placed in a tube furnace and heated to 200℃ at a flow rate of 300 sccm in a N2 atmosphere at a rate of 5℃ / min, and held for 2 h, then heated to 600℃~900℃ and held for 2 h, and then cooled to room temperature to obtain un-acid-washed MIL / ZIF-x-700℃ powder; the un-acid-washed MIL / ZIF-x-700℃ was acid-washed in 3M HNO3, sonicated at 80℃ for 2 h, and allowed to stand for 8 hours. h; then the sample was vacuum extracted and filtered with deionized water to make the sample neutral, and then placed in a vacuum drying oven at 40℃ for 12 h; finally, the acid-washed MIL / ZIF-x-700℃ powder was obtained, and the acid-washed MIL / ZIF-x-700℃ was placed in a tube furnace, heated to a certain temperature in a mixed gas atmosphere, held for 2 h, and then cooled to room temperature to finally obtain MIL / ZIF-x-700℃-NH3 powder.
2. The preparation method according to claim 1, characterized in that... In step S3, the mixed gas is ammonia and nitrogen.
Citation Information
Patent Citations
Zinc-based metal organic framework material, preparation method of iron-nitrogen co-doped carbon-based oxygen reduction electrocatalyst and application
CN110534755A
Preparation method of bimetallic nitrogen-containing porous carbon catalyst
CN115020722A